Infectiousness of patients with smear-negative pulmonary tuberculosis, assessed by Real-time Polymerase Chain Reaction, XpertⓇMTB/RIF. Issue 3 (March 2020) - Camprubí, Daniel; Gomila, Aina; Grijota-Camino, Maria D.; Soldevila, Laura; Luque, Maria J.; Alcaide, Fernando; Dorca, Jordi; Santin, Miguel
Highlights: There are no statistically significant differences in rates of M. tuberculosis infection between contacts of smear-positive and contacts of Sm-/GXpert+ pulmonary TB patients. Sm-/GXpert+ pulmonary TB poses a substantial risk of transmission of M. tuberculosis infection. Real-time Polymerase Chain Reaction (Xpert Ⓡ MTB/RIF) should be included in the work-up diagnosis of suspected pulmonary TB cases to make decisions on air-borne isolation. Abstract: Currently, pulmonary tuberculosis (TB) isolation recommendations are based on serial sputum smear microscopy. To assess infectiousness of smear-negative/GeneXpert-positive (Sm-/GXpert+) pulmonary TB, we evaluated 511 contacts of pulmonary TB patients attended at a teaching hospital in Spain (2010–2018). There were no statistically significant differences in rates of Mycobacterium tuberculosis infection (46.2% contacts of smear-positive and 34.6% contacts of Sm-/GXpert+ pulmonary TB patients, p = 0.112). Sm-/GXpert+ pulmonary TB poses a substantial risk of transmission of M. tuberculosis infection. Our results add evidence to support including Real-time Polymerase Chain Reaction (Xpert Ⓡ MTB/RIF) in the work-up diagnosis of suspected pulmonary TB cases to make decisions on air-borne isolation.